2006
DOI: 10.1152/ajpcell.00011.2006
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic regulation by bile acids of dermal fibroblast proliferation through regulation of cAMP production and COX-2 expression level

Abstract: -We have previously reported that the bile acids chenodeoxycholate (CDCA) and ursodeoxycholate (UDCA) decreased PGE1-induced cAMP production in a time-and dose-dependent manner not only in hepatocytes but also in nonhepatic cells, including dermal fibroblasts. In the present study, we investigated the physiological relevance of this cAMP modulatory action of bile acids. PGE1 induced cAMP production in a time-and dosedependent manner. Moreover, PGE1 (1 M), forskolin (1-10 M), and the membrane-permeable cAMP ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Extrapolation of data from cancer studies (40)(41)(42)(43)(44)(45) suggested the possibility that a CDCA-Wnt/␤-catenin or a CDCA-COX2-Wnt/␤-catenin pathway might function in the healthy intestinal epithelium and drive AMPP synthesis. Expression of Ptgs2 (Cox2) in the ileum was in fact upregulated by CDCA feeding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Extrapolation of data from cancer studies (40)(41)(42)(43)(44)(45) suggested the possibility that a CDCA-Wnt/␤-catenin or a CDCA-COX2-Wnt/␤-catenin pathway might function in the healthy intestinal epithelium and drive AMPP synthesis. Expression of Ptgs2 (Cox2) in the ileum was in fact upregulated by CDCA feeding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of adenylate cyclase by bile acids increases cellular cAMP in many cells (21)(22)(23); however, whether this occurs in hepatocytes is unknown. Because taurocholate-accelerated canalicular network formation is adenylate cyclase-dependent ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, we found that dermal fibroblasts are less sensitive to the antimitogenic effect of PGE 2 than gingival fibroblasts. Prostaglandin E 2 inhibits proliferation of many cell types, including fibroblasts from various sources (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), and in several of these cells it was shown to operate via the EP 2 receptor and cAMP generation (10,12,14,(16)(17)(18). Like GFs (48), DFs express all four EP receptors (49) and, since PGE 2 causes cAMP production in DFs (50), it is reasonably safe to assume that EP 2 also mediates the inhibitory effect of PGE 2 on DF proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…However, exaggerated local production of PGs due to trauma or infection of the wound may interfere with proper cutaneous healing. In addition to its recognized role in the inflammation per se , PGE 2 has documented antiproliferative effects on gingival (7–10) and dermal fibroblasts (11,12) as well as on fibroblasts from other sources [tendon (13), lung (14), embryonic (15) and liver (16)] and on other cell types, such as gastric carcinoma cells (17) and arterial smooth muscle cells (18). Interestingly, there are no solid data on whether PGE 2 affects the proliferation of gingival epithelial cells (keratinocytes).…”
mentioning
confidence: 99%